Definitive radiotherapy for local and metastatic lesions in prostate cancer patients with oligometastases - Xu, Bichun; Zhao, Xianzhi; Liang, Yiyin; Zhang, Weiwei; Chen, Liang; Ye, Yusheng; He, Jie; Tong, Jiaojiao; Gong, Yangyang; Luo, Judong; Zhang, Huojun (Frontiers in Oncology, 2025)
BackgroundFew studies explore the role of definitive radiotherapy for prostate and all metastases in the treatment of low-burden oligometastatic prostate cancer (omPCa). This study aimed to investigate the potential survival benefit of this approach. Moreover, it is the first study to report the outcomes of definitive radiotherapy for local and distant metastatic lesions in patients with omPCa from China.MethodsA retrospective analysis was conducted on patients with omPCa who received definitive radiotherapy for the primary site and metastatic lesions between July 2012 and June 2022. The inclusion criteria mandated fewer than 5 oligometastases, excluding regional lymph nodes by imaging examinations with no prior radiotherapy or radical prostatectomy for omPCa. Overall survival (OS) was the primary endpoint, and biochemical progression-free survival (bPFS) and radiological progression-free survival (rPFS) were the secondary endpoint. The Kaplan-Meier method was used to estimate survival rates. Univariate and multivariate analyses were conducted using Cox proportional hazards regression models.ResultsA total of 33 patients, including 31 de novo oligometastatic hormone-sensitive prostate cancer (omHSPC) patients and 2 oligometastatic castration-resistant prostate cancer (omCRPC) patients, were enrolled in the study. The median follow-up was 38.8 months (range: 4.2–70.6 months). The OS rates of 2-, 3-, and 5-year after treatment were 100.0%, 95.7%,and 81.2%, respectively. Factors correlating with poorer survival were pre-radiotherapy CRPC status, symptomatic lesions, and prior transurethral resection of the prostate (TURP). Multivariate analysis revealed potential associations: concomitant androgen deprivation therapy (ADT) or chemotherapy, non-CRPC status pre-radiotherapy. Lymph node and bone metastases together increased the risk of biochemical recurrence. Acute adverse reactions of Grade 3+ were absent; chronic Grade 3 reactions were 3.0%.ConclusionDefinitive radiotherapy for local/metastatic lesions demonstrates promising survival with manageable toxicity in omPCa.